2018
DOI: 10.1186/s13643-018-0821-7
|View full text |Cite
|
Sign up to set email alerts
|

Just how plain are plain tobacco packs: re-analysis of a systematic review using multilevel meta-analysis suggests lessons about the comparative benefits of synthesis methods

Abstract: BackgroundComparisons between narrative synthesis and meta-analysis as synthesis methods in systematic reviews are uncommon within the same systematic review. We re-analysed a systematic review on the effects of plain packaging of tobacco on attractiveness. We sought to compare different synthesis approaches within the same systematic review and shed light on the comparative benefits of each approach.MethodsIn our re-analysis, we included results relating to attractiveness in included reports. We extracted fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Avoidance of the term “narrative synthesis” in SWiM is a deliberate move to promote clarity in the methods used in reviews in which the synthesis does not rely on meta-analysis. The use of narrative is ubiquitous across all research and can serve a valuable purpose in the development of a coherent story from diverse data 3334. However, within the field of evidence synthesis, narrative approaches to synthesis of quantitative effect estimates are characterised by a lack of transparency, making assessment of the validity of their findings difficult 7.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of the term “narrative synthesis” in SWiM is a deliberate move to promote clarity in the methods used in reviews in which the synthesis does not rely on meta-analysis. The use of narrative is ubiquitous across all research and can serve a valuable purpose in the development of a coherent story from diverse data 3334. However, within the field of evidence synthesis, narrative approaches to synthesis of quantitative effect estimates are characterised by a lack of transparency, making assessment of the validity of their findings difficult 7.…”
Section: Discussionmentioning
confidence: 99%
“…Studies mainly indicate that plain packaging increases the salience of health warnings and pictorials. The pictorials on plain packages are noticed more easily, recalled better and have a stronger impact 7,10,15,17,19,20,[28][29][30]36,37 . Our results also indicate that the effects of the pictorials are more profound in the plain packs compared to the branded ones.…”
Section: Discussionmentioning
confidence: 97%
“…Narrative and quantitative syntheses are the two most commonly used approaches for synthesizing data in evidence synthesis 5 . There are some published studies on the proposed indications and implications of these two approaches 30,31 . These studies found that both data synthesis methods produced comparable results and have their own advantages, suggesting that the choice of the method must be based on the purpose of the review 31 .…”
Section: Discussionmentioning
confidence: 99%
“…5 There are some published studies on the proposed indications and implications of these two approaches. 30,31 These studies found that both data synthesis methods produced comparable results and have their own advantages, suggesting that the choice of the method must be based on the purpose of the review. 31 With increasing number of "expedited" SR approaches (so called "rapid reviews") avoiding MA, 10,11 further research studies are warranted in this area to determine the impact of the type of data synthesis on the results of the SR.…”
Section: Summary Of Findingsmentioning
confidence: 99%